2022
DOI: 10.55251/jmbfs.4622
|View full text |Cite
|
Sign up to set email alerts
|

BACTERIAL INHIBITORY EFFECT OF ALGERIAN POMEGRANATE (Punica Granatum L.) EXTRACTS (PEEL, JUICE, AND SEED) AGAINST MULTIDRUG RESISTANT BACTERIA

Abstract: Punica granatum L. (pomegranate) is known popularly by its nutritional values and healthy benefits. The current study is aimed the evaluation of antibacterial effects of Punica granatum fruit extracts that cultivated in Algeria against environmental and clinical isolates of β-lactamase producing methicillin resistant Staphylococcus aureus (MRSA) and extended-spectrum beta-lactamase ESBL-producing Enterobacteriaceae by using agar diffusion methods and minimum inhibitory concentration (MIC)-determination. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…Besides, the BP had an effect on B. cereus, S. aureus and P. aeruginosa with MBC values of 50, 100 and 100 mg/mL, respectively. In previous study, Debib et al 69 showed that petroleum ether, ethanolic and acetonic peel extracts inhibited the growth of E. coli with inhibition zones ranging from 14 to 28 mm and MIC values ranging from 8 to 256 μg/mL; in contrast, our fractions did not show any effect against this bacteria. The activity of pomegranate peels against microbes can be attributed to its high polyphenolic content, particularly its flavonoids and tannins.…”
Section: Antibacterial Activitycontrasting
confidence: 52%
See 1 more Smart Citation
“…Besides, the BP had an effect on B. cereus, S. aureus and P. aeruginosa with MBC values of 50, 100 and 100 mg/mL, respectively. In previous study, Debib et al 69 showed that petroleum ether, ethanolic and acetonic peel extracts inhibited the growth of E. coli with inhibition zones ranging from 14 to 28 mm and MIC values ranging from 8 to 256 μg/mL; in contrast, our fractions did not show any effect against this bacteria. The activity of pomegranate peels against microbes can be attributed to its high polyphenolic content, particularly its flavonoids and tannins.…”
Section: Antibacterial Activitycontrasting
confidence: 52%
“…70 One of the anti-infective properties of tannins is causing membrane instability, 56 and for flavonoids is forming complexes with various proteins found inside the bacterial cell walls or extracellular proteins, 68 consequently, causing leakage of the cell membrane and cell lysis, which ultimately leads to microorganism death. 69 The results above indicate the richness of AP and BP in tannins and flavonoids, in addition to the efficient capacities of extracts as antioxidants, which may explain their antibacterial effect (inhibition zone: 13-25 mm, MIC: 0.39-12.5 mg/mL and MBC: 25-100 mg/mL). The good activity of BP against P. aeruginosa may be interpreted by the higher content of flavonoids and flavonols compared to the ethyl acetate fraction.…”
Section: Antibacterial Activitymentioning
confidence: 81%
“… 14 , 16 Components of pomegranate influence transcription factors, anti-apoptotic proteins, pro-apoptotic proteins, cell cycle regulator molecules, pro-inflammatory mediators, cell adhesion molecules, protein kinases, and growth factors in multiple types of cancer. 19 …”
Section: Introductionmentioning
confidence: 99%
“…14,16 Components of pomegranate influence transcription factors, anti-apoptotic proteins, pro-apoptotic proteins, cell cycle regulator molecules, pro-inflammatory mediators, cell adhesion molecules, protein kinases, and growth factors in multiple types of cancer. 19 The ongoing work's aim was to trace the pomegranate seed and peel ethanolic extracts' anticancer activity against liver cancer cell line, namely HepG2 and related histopathological, immunohistochemical, genetic and oxidative stress profile.…”
Section: Introductionmentioning
confidence: 99%
“…The interesting fact is that peel extract has the highest amount of bioactive phenolic compounds such as ellagitannins, tannins [28] and anthocyanin [29,30], including ellagic acid as well as punicalagin (2,3-hexahydroxydiphenoylgallagyl-D-glucose) [31]. Recently, pomegranate extracts were evaluated against beta-lactamase-producing drug resistance Gram-positive and Gram-negative bacteria using agar diffusion and minimum inhibitory concentration assays [27,32].…”
Section: Introductionmentioning
confidence: 99%